PENGARUH POTENSI DIRI, PERENCANAAN KARIR, LINGKUNGAN TEMAN SEBAYA DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA KELAS XII MAN 1 PASAMAN BARAT MELALUI MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING - Risdaini; Jolianis; Rahmania, Meri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine: 1) the influence of self-potential on students' motivation to continue their studies at university, 2) the influence of career planning on students' motivation to continue their studies at university, 3) the influence of peer groups on students' motivation to continue their studies at university, 4) the influence of parents' socioeconomic status on students' motivation to continue their studies at university, 5) the influence of self-potential on students' interest in continuing their studies at university, 6) the influence of career planning on students' interest in continuing their studies at university, 7) the influence of peers on students' interest in continuing their studies at university, 8) the influence of parents' socioeconomic status on students' interest in continuing their studies at university, 9) the influence of learning motivation on students' interest in continuing their studies at university. This type of research is descriptive and associative. This research was conducted at MAN 1 West Pasaman. The total population and sample were 67 students. The data types were primary and secondary data. Data collection techniques were observation, questionnaires, and documentation. The data analysis technique was path analysis tested using SPSS 21 software. The results of the study show that: 1). Self-potential does not have a significant effect on learning motivation with a path coefficient value of 0.240 with a significance value of 0.257 > 0.05. 2). Career planning has a significant effect on learning motivation with a path coefficient value of 0.579 with a significance value of 0.003 ˂ 0.05. 3). Peer environment does not have a significant effect on learning motivation with a path coefficient value of 0.019 with a significance value of 0.914 > 0.05. 4). Parents' socioeconomic status does not significantly influence learning motivation with a path coefficient value of 0.404 with a significant value of 0.124 > 0.05. 5). Self-potential has a significant influence on the interest in continuing studies to college with a path coefficient value of 0.447 and a significant value of 0.001 ˂ 0.05. 6). Career planning has a significant influence on the interest in continuing studies to college with a path coefficient value of 0.379 and a significant value of 0.003 ˂ 0.05. 7). Peer environment does not significantly influence the interest in continuing studies to college with a path coefficient value of 0.114 and a significant value of 0.292 > 0.05. 8). Parents' socioeconomic status does not significantly influence the interest in continuing studies to college with a path coefficient value of 0.055 and a significant value of 0.737 > 0.05. 9). Learning motivation influences the interest in continuing studies to college with a path coefficient value of 0.251 and a significant value of 0.002 ˂ 0.05.